ANALISIS SWOT PADA MARKETING/BISNIS - Listiya Andana Lubis; Nadya Maulidya Manurung; Nurbaiti Nurbaiti (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2021)
SWOT analysis is a method in which a strategy design is used to assess the strength, weaknesses, oppurtunities, threats or SWOT of project as well as a business venture. E-commerce is the implementation and management of critical business processess such as product design, material procurement, production, sales and ordering. Provide and fulfill services through the use of communication technology, computers and service provision. This research was carried out aiming to find out how the company runs its business with a solid marketing strategy through SWOT analysis. In this study, the authors chose several analytical methods, such as data collection methods, discussion methods, conclusion methods, research types and approaches, data collection sources and methods, and data analysis methods. The conclusion of Thompson's (2008) research is that SWOT analysis is very simple, but it uses a very powerful tool to improve skills and external threats to company resources, market opportunities, and a bright future. Find inefficiencies. Management of raw material supply design, manufacturing and sales), computer-aided communication, order processing, and service provision using computer technology and data.